Recent Advances in Nanoencapsulated and Nano-Enhanced Phase-Change Materials for Thermal Energy Storage: A Review - Khlissa, Faïçal; Mhadhbi, Mohsen; Aich, Walid; Hussein, Ahmed Kadhim; Alhadri, Muapper; Selimefendigil, Fatih; Öztop, Hakan F.; Kolsi, Lioua (Processes, 2023)
Phase-change materials (PCMs) are becoming more widely acknowledged as essential elements in thermal energy storage, greatly aiding the pursuit of lower building energy consumption and the achievement of net-zero energy goals. PCMs are frequently constrained by their subpar heat conductivity, despite their expanding importance. This in-depth research includes a thorough categorization and close examination of PCM features. The most current developments in nanoencapsulated PCM (NEPCMs) techniques are also highlighted, along with recent developments in thermal energy storage technology. The assessment also emphasizes how diligently researchers have worked to advance the subject of PCMs, including the creation of devices with improved thermal performance using nano-enhanced PCMs (NEnPCMs). This review intends to highlight the progress made in improving the efficiency and efficacy of PCMs by providing a critical overview of these improvements. The paper concludes by discussing current challenges and proposing future directions for the continued advancement of PCMs and their diverse applications.